Respuesta :
An equation would be 6x-5+56=6+34x.
Step 1: Simplify both sides of the equation.6x−5+56=6+34x6x+−5+56=6+34x(6x)+(−5+56)=34x+6
(Combine Like Terms)6x+51=34x+66x+51=34x+6Step 2: Subtract 34x from both sides.6x+51−34x=34x+6−34x−28x+51=6Step 3: Subtract 51 from both sides.−28x+51−51=6−51−28x=−45Step 4: Divide both sides by -28.−28x−28=−45−28x=1 17/28
I hope this helped! ♡
Step 1: Simplify both sides of the equation.6x−5+56=6+34x6x+−5+56=6+34x(6x)+(−5+56)=34x+6
(Combine Like Terms)6x+51=34x+66x+51=34x+6Step 2: Subtract 34x from both sides.6x+51−34x=34x+6−34x−28x+51=6Step 3: Subtract 51 from both sides.−28x+51−51=6−51−28x=−45Step 4: Divide both sides by -28.−28x−28=−45−28x=1 17/28
I hope this helped! ♡